Replacement of Palm Methyl Ester to Rapeseed Methyl Ester for Tar Removal in the Nong Bua Dual Fluidized Bed Gasification Power Plant. Issue 1 (June 2021) - Tonpakdee, P; Hongrapipat, J; Siriwongrungson, V; Pang, S; Rauch, R; Messner, M; Henrich, C; Pessl, P; Dichand, M
Abstract: The blockage problem of tar in a biomass power plant is a main problem and it must be removed. Rapeseed methyl ester (RME) was imported and used as scrubbing solvent to scrub tar at a 1 MWel Nong Bua prototype Dual Fluidised Bed (DFB) gasifier in Nong Bua district, Nakhonsawan province, Thailand. Using local oil in Thailand is an attractive choice from economic viewpoint. Pervious lab test study on naphthalene solubility in different local oils in Thailand was investigated. Local palm methyl ester (PME) shows the competitive performance to the RME. In this research, PME was tested to scrub tar in an oil scrubber at the Nong Bua DFB gasifier plant. Gravimetric tar content after passed a PME scrubber was measured and compared to that from a RME oil scrubber. The results show that both solvents have similar tar removal performance due to their contents of ester, methanol, and glycerin are similar. In addition, viscosity of both solvents has no significant effect on tar removal. From the current research, therefore, PME has been used as solvent in an oil scrubber at 1 MWel Nong Bua prototype DFB gasifier with technical and economic reasons.